2018
DOI: 10.1016/j.nanoen.2018.01.012
|View full text |Cite
|
Sign up to set email alerts
|

High-performance all-polymer solar cells based on fluorinated naphthalene diimide acceptor polymers with fine-tuned crystallinity and enhanced dielectric constants

Abstract: Growing interests have been devoted to the synthesis of polymer acceptors as alternatives to fullerene derivatives to realize high-performance and stable all-polymer solar cells (all-PSCs). So far, one of the key factors that limit the performance of all-PSCs is low photocurrent density (normally < 2 14 mA/cm 2). One potential solution is to improve the dielectric constants (ε r) of polymer:polymer blends, which tend to reduce the binding energy of excitons, thus boosting the exciton dissociation efficiencies.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
77
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 104 publications
(77 citation statements)
references
References 72 publications
0
77
0
Order By: Relevance
“…The PBDB‐T‐2Cl:IT4F‐ and PBDB‐T:IT4F‐based binary devices separately exhibit the higher average ε r of 3.54 and 3.40 with respect to PBDB‐T‐2Cl:ITIC (3.08) and PBDB‐T:ITIC (3.26) systems, suggesting that fluorination of nonfullerene acceptors can enhance the dielectric constants of blend films. This might originate from the strong intramolecular dipole and increased polarizability of IT4F molecules . In addition, the highest ε r for PBDB‐T‐2Cl:IT4F blend could be ascribed to the more ordered molecular packing of both the chlorine‐containing donor and fluorine‐containing acceptor, supporting the easier reorientations for molecular dipole moments in BHJ films …”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…The PBDB‐T‐2Cl:IT4F‐ and PBDB‐T:IT4F‐based binary devices separately exhibit the higher average ε r of 3.54 and 3.40 with respect to PBDB‐T‐2Cl:ITIC (3.08) and PBDB‐T:ITIC (3.26) systems, suggesting that fluorination of nonfullerene acceptors can enhance the dielectric constants of blend films. This might originate from the strong intramolecular dipole and increased polarizability of IT4F molecules . In addition, the highest ε r for PBDB‐T‐2Cl:IT4F blend could be ascribed to the more ordered molecular packing of both the chlorine‐containing donor and fluorine‐containing acceptor, supporting the easier reorientations for molecular dipole moments in BHJ films …”
Section: Resultsmentioning
confidence: 87%
“…The PBDB‐T‐2Cl:IT4F‐based devices present the smallest r c of 15.81 nm among four binary systems at room temperature, indicating that simultaneous introduction of chlorination and fluorination can reduce the probability of bimolecular recombination, further supporting the highest J SC , FF, and EQE values. More impressively, the increased dielectric constant in PBDB‐T‐2Cl:IT4F BHJ could decrease the binding energy of the CT state, thus motivating more efficient charge separation …”
Section: Resultsmentioning
confidence: 99%
“…[35] The kinetic Monte Carlo (kMC) method is a powerful simulation technique to model the time-dependent behavior of physical systems. [11,12,[51][52][53][54][55][56][57][58][59][60] In addition, pristine organic materials with low energetic disorder support separation dynamics: a low disorder leads to a more ballistic transport and more efficient separation. [36] A specific advantage of the kMC method is that it allows to include explicit particle-particle interactions and that it gives direct access to the charge trajectories which can be used to assess the CP displacement from the heterojunction.…”
Section: Wwwadvtheorysimulcommentioning
confidence: 99%
“…All‐polymer OSCs based on polymer donors and acceptors are quite promising for practical applications, owing to their advantages of highly adjustable chemical and electronic properties and excellent morphological stabilities and mechanical properties . Recently, great progress has been made in the development of all‐polymer OSCs and PCEs of over 11 % have been achieved, owing to the rapid development of polymer acceptors, especially fluorinated polymer acceptors . This section briefly summarizes and discusses the design and structure–property relationships of fluorinated polymer acceptors that have been applied in OSCs.…”
Section: Introductionmentioning
confidence: 99%
“…Later, Wang et al. synthesized a fluorinated polymer, PNDI‐FT10, by introducing a monothiophene unit into the backbone of P(NDI2OD‐FT2) . It was found that PNDI‐FT10 had increased dielectric constants compared with that of its non‐fluorinated analogue; this tended to boost the exciton dissociation efficiency and PCE (7.3 %) of OSCs.…”
Section: Introductionmentioning
confidence: 99%